2018
DOI: 10.4049/jimmunol.1701188
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Complexities of Tumor-Associated Regulatory T Cells

Abstract: Regulatory T (Treg) cells are found at elevated densities in many human cancers and are thought to be a major barrier to the generation of robust antitumor T cell responses. In this review, we discuss recent advances in the understanding of tumor-associated Treg cell diversity and function. Emerging evidence indicates that the transcriptional program of Treg cells infiltrating human cancers may represent a composite program blending a tissue-associated expression signature with an additional tumor-specific sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 48 publications
2
54
0
Order By: Relevance
“…Depletion of Treg cells by targeting the chemokine receptor CCR4 can induce melanoma antigen-specific immune responses in vitro (37), but the mechanism of action as well as the specificity of this approach to intratumoral Treg cells remain incompletely understood. Several studies in animal models have shown that intratumoral Treg cells can be selectively depleted by antibodies that target CTLA-4, GITR, and OX40, owing to the elevated expression of these markers by tumor-infiltrating Treg cells (38). It has been suggested that the mechanism of action of ipilimumab in patients with melanoma may involve depletion of CTLA-4 expressing Treg cells through antibody-dependent cell-mediated cytotoxicity by nonclassical monocytes (39).…”
Section: The Potential Of Treg Cell-targeted Immunotherapiesmentioning
confidence: 99%
“…Depletion of Treg cells by targeting the chemokine receptor CCR4 can induce melanoma antigen-specific immune responses in vitro (37), but the mechanism of action as well as the specificity of this approach to intratumoral Treg cells remain incompletely understood. Several studies in animal models have shown that intratumoral Treg cells can be selectively depleted by antibodies that target CTLA-4, GITR, and OX40, owing to the elevated expression of these markers by tumor-infiltrating Treg cells (38). It has been suggested that the mechanism of action of ipilimumab in patients with melanoma may involve depletion of CTLA-4 expressing Treg cells through antibody-dependent cell-mediated cytotoxicity by nonclassical monocytes (39).…”
Section: The Potential Of Treg Cell-targeted Immunotherapiesmentioning
confidence: 99%
“…If the dwell time of the TCR on the pMHC is of sufficient duration, a T cell will become activated and differentiate to helper (Th), cytotoxic (CTL), regulatory (Treg), or memory (Tm) T cells that are essential for long-lived immunity 1,2 . CD4 + Th subsets provide help for effective CTL, B cell, and innate immune cell function upon immunologic challenge, Tregs are crucial for peripheral tolerance to self and commensal antigens, Tm allow for rapid antigen-specific responses, and CTLs can eliminate infected or cancerous cells 36 . However, the activity of each T cell subset can be counter-productive if conditions are such that they result in the induction of allergies, asthma, autoimmunity, transplant rejection, or, in the case of Tregs, the protection of tumors.…”
Section: Mainmentioning
confidence: 99%
“…Tumor stromal cells including cells of the immune system modulate cancer development and progression . Regulatory T (Treg) cells that express the transcription factor FOXP3 are often found at elevated levels in tumor lesions and are essential for the prevention of autoimmunity and the maintenance of immune homeostasis . Moreover, the density of tumor‐infiltrating Treg cells has prognostic value and can be negatively or positively correlated with the outcome of several malignancies, depending on the cancer type …”
Section: Introductionmentioning
confidence: 99%